NURSES' KNOWLEDGE WITH THE IMPLEMENTATION OF PRIMARY SURVEY ON EMERGENCY PATIENTS - Eka Nur So'emah; Emyk Windartik; Ima Rahmawati (Kirana Publisher, 2023)
Emergencies happen suddenly and cannot be predicted when they will happen. Life-threatening emergency problems can be carried out first aid measures through primary survey. Nurses are at the forefront of providing first aid and need to equip themselves with knowledge about primary surveys that affect the success of efforts to help patients. The purpose of this study was to determine the relationship between the level of nurse knowledge and the implementation of the primary survey. This research method is Literature Review. Searching database research journals using certain keywords in the period 2011-2019. In the search, 10 journals were obtained that met the inclusion criteria and then reviewed. Several main results from the literature review were obtained, one of which was the results of research (Massa, 2018) showing a positive correlation value obtained a significance value of 0.000 or p <0.05 with a correlation coefficient value of 0.743. This shows that there is a relationship between nurse knowledge and the implementation of primary surveys in emergency patients. Thus it can be concluded that to support a person's actions, knowledge or cognitive is needed for the smooth running of primary survey actions in emergency patients. The solution that can be obtained is to plan a programme to increase the knowledge and skills of nurses by holding a training, so that the application of primary survey actions can be done quickly, precisely and carefully.